Udawanie i zabawa jako formy zaangażowanie religijnego - Sztajer, Sławomir (Humaniora. Czasopismo Internetowe, 2021)
Pretense and play are present in a variety of religious traditions. They are used in religious thinking about the world as well as in ritual behavior. As a form of simulation, pretense and play are more than cultural forms because they occur in human and animal behavior. Simulation is based on complex cognitive and communicative processes and requires metacognitive and metacommunicative abilities. In religious practice, pretense and play tend to turn into serious and “authentic” behavior accompanied by the sense of reality characteristic for religious experience. It seems that the ability to cross the frames of pretense and play towards seriousness and authenticity is part of the logic of simulation. Categories of pretense and play can be used to explain the dynamic character of religious faith. The latter can be understood as shifting between two modes of experience: the reality mode (the world seen as “it is”) and the simulation mode (the world of “as if”).